2006
DOI: 10.1128/jb.188.7.2421-2426.2006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Culture Heterogeneity in Cell Surface Charge on Adhesion and Biofilm Formation by Enterococcus faecalis

Abstract: Biofilm formation is an increasing problem in medicine, due to the intrinsic resistance of microorganisms in the biofilm mode of growth against the host immune system and antimicrobial therapy. Adhesion is an important step in biofilm formation, influenced, among other factors, by the surface hydrophobicities and charges of both the substratum and the adhering microorganisms. Enterococcus faecalis strains generally display subpopulations with different surface charges, expressed as bimodal zeta potential distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 30 publications
2
65
1
Order By: Relevance
“…35,36 As an example, in preliminary experiments we have also observed the self-organising process with mesenchymal stem cells (data not shown). Since a washing step might selectively inuence the heterogeneity of surface adhesion, [37][38][39] our assay can also be applied to weakly adherent cells that need more time to settle down. Having to wait several hours for selforganization might seem to be incompatible with highthroughput studies, but commonly used approaches also require 2 to 15 h to allow cells to adhere on the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 As an example, in preliminary experiments we have also observed the self-organising process with mesenchymal stem cells (data not shown). Since a washing step might selectively inuence the heterogeneity of surface adhesion, [37][38][39] our assay can also be applied to weakly adherent cells that need more time to settle down. Having to wait several hours for selforganization might seem to be incompatible with highthroughput studies, but commonly used approaches also require 2 to 15 h to allow cells to adhere on the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Since Atn is important for cellular growth as well as cell lysis, the adherence defect observed after atn deletion could be the result of increased chaining of the mutants (9, 57), leading to a reduction in binding sites or an increase in cell surface charges, causing a lower cell deposition rate. Repulsive interactions between abiotic surfaces and bacteria, as well as between adhered cells and incoming cells, due to surface charges were shown to influence the initial adhesion of bacteria to substrata (73). Alternatively, defects in autolytic processes may result in modification of the cell wall structure and mislocalization of surface proteins required for attachment during biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for both E. faecium and E. faecalis, isolates were found that carried the esp gene but that failed to produce biofilms. Esp-independent biofilm formation by E. faecalis is probably mediated by multiple additional factors, like GelE (12,16,25), BopD (13), the fsr locus (12), the bee locus (37), and heterogeneity in surface charge (43). The observations that biofilms produced by E. faecalis are much thicker than those produced by E. faecium and that the biofilm development of E. faecalis is much more sensitive to the growth medium used (29) may indicate that in E. faecalis, additional factors aside from Esp are involved.…”
Section: Discussionmentioning
confidence: 99%
“…In E. faecalis, several other factors have been associated with biofilm development, like the sugar-binding transcriptional regulator BopD (13), the quorum-sensing locus fsr (12), heterogeneity in surface charge (43), the bee locus (37), and the secreted metalloprotease GelE (12,16,25). Yet absence of a correlation between gelatinase and biofilm development has also been found (6,21,43).…”
mentioning
confidence: 99%